Association of nutrition club membership with markers of health: a cross sectional study - Sai Krupa Das; Taylor A. Vail; Namibia Lebrón-Torres; Kara A. Livingston; Susan B. Roberts; Gail T. Rogers; Cheryl H. Gilhooly; Lorien E. Urban; Edward Saltzman; Nicola M. McKeown; Sara C. Folta (BMC, 2017)
Abstract Background Nutrition clubs (NC) operate in community settings and provide members with nutrition education and meal replacements for weight management. NC are owned and operated by distributors of Herbalife products. There are over 6200 NC in the US, but there has been no independent assessment of the association of these NC with biomarkers of health. Methods We conducted a cross-sectional pilot study to compare the health status of 100 NC members to 100 community-matched controls (CC) in the greater Boston area. Each CC was matched to a NC member for community of residence (zip code), age category, gender, BMI category, race/ethnicity, education level (category), and readiness to make health changes. Measures obtained included cardio-metabolic risk factors, body composition, markers of nutritional status, reported health status, dietary intake, physical activity, sleep and depression. Results Participants were predominantly female (64%) and Hispanic (73%). NC members had significantly lower fasting insulin (P < 0.001) and lower HbA1c (P = 0.008), higher levels of 25 hydroxy-vitamin D (P = 0.001), and vitamin E:cholesterol ratio (P < 0.001), and lower prevalence of metabolic syndrome (P = 0.02) compared to CC. In addition, most of the NC members (99%) were satisfied with Herbalife NC membership for themselves and their families. A higher percentage of NC members (86%) compared to CC (32%) reported being in much better or somewhat better health compared to a year ago (P < 0.001); and they reported significantly better physical health (P = 0.03), and fewer sleep problems (P = 0.03). Conclusion Herbalife NC membership was positively associated with perceived health and measured cardiometabolic benefits. However, causality cannot be inferred from these findings.